Mayim's vegan table : more than 100 great-tasting and healthy recipes from my family to yours. - Bialik, Mayim (Da Capo Press, Incorporated, 2014)
While she's an actress with a PhD in neuroscience, at the end of the day Mayim Bialik is a mom, one who knows what it's like to be a busy parent with little time to spend in the kitchen. She shares the concerns of parents everywhere: when it comes to nutrition and feeding your family, you want healthy meals, but also food that everyone can enjoy, and a balanced lifestyle that's inexpensive and fuss-free. Not only does this book shares more than 100 easy plant-based recipes, but Mayim has also teamed up with pediatrician Jay Gordon to offer basic nutritional information about a plant-based diet; the real deal on raising kids on a plant-based diet; vegan family essentials (including a list of what to always keep in the pantry); as well as tips and strategies for easy meal planning and healthy eating out.